Validation of thin film TiO2 optical constants by reflectometry and ellipsometry in the VUV spectral range. (26th February 2019) - Gottwald, Alexander; Wiese, Karl; Siefke, Thomas; Richter, Mathias
Abstract: Optical constants of thin films in the vacuum ultraviolet spectral range are often not precisely known, since not only the experimental determination is difficult, but also the results depend on the sample preparation. We compared measurements in the wavelength interval between 130 nm and 226 nm using reflectometry and ellipsometry with particular regard to their respective uncertainty budgets. Since for both methods a numerical analysis is required to obtain the optical constants from the measured data, particular attention was paid to the error propagation through the calculation routines, and the uncertainties introduced by the numerical methods and models themselves. The measurement methods were applied to a thin layer of 6 nm titania (TiO2 ) on a silicon substrate. The result is used to validate our method, and to identify further analytical requirements.